Land Use Transition and Its Eco-Environmental Effects in the Beijing–Tianjin–Hebei Urban Agglomeration: A Production–Living–Ecological Perspective - Yuanyuan Yang (Land, 2020)
With the rapid development of urbanization and industrialization, China’s metropolitan areas have experienced dramatic transitions of land use, which has had a profound impact on the eco-environment. Accordingly, the contradictions of regional production, living, and ecological spaces have intensified. In this context, analysis of the dynamics of regional production–living–ecological (PLE) spaces has become an important entry point for studying land use transition and its eco-environmental effects, by constructing a classification system of PLE land functions. Using remote sensing data from four periods from 1985 to 2018, this paper explores the spatiotemporal evolution characteristics of PLE spaces and their eco-environmental effects in the Beijing–Tianjin–Hebei (BTH) urban agglomeration, based on GIS and the InVEST model. The results revealed that from 1985 to 2018, the living space of the BTH region expanded rapidly, the production space gradually shrank, and the ecological land remained relatively stable. The eco-environmental quality index within the study area shows obvious regional differences, demonstrating the spatial distribution of “high in the northwest and low in the southeast”, and an overall deteriorating trend in the past 33 years. Moreover, the carbon density decreased gradually from northwest to southeast, and the transformations from production land into living land and from ecological land into production land were the major types of eco-environment deterioration. Our findings will provide guidelines for land use management, and offer references for the functional division of PLE spaces and ecological civilization construction, especially in terms of the coordinated development of the BTH region.